2021
DOI: 10.1177/0890117121995776
|View full text |Cite
|
Sign up to set email alerts
|

The Longitudinal Association Between Exposure to Violence and Patterns of Health Risk Behaviors Among African American Youth

Abstract: Purpose: We investigate whether exposure to violence (ETV) during adolescence and emerging adulthood predicts engagement in chronic disease-related health risk behaviors years later among African Americans. Design: A longitudinal study following youth from mid-adolescence (mean age = 14.8 years) to young adulthood (mean age = 32.0 years). Setting: Flint, Michigan. Sample: Four hundred forty-two African American (96.2%) and mixed African American and White (3.8%) participants. Measures: Outcomes were diet, smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Since we found time by condition interaction effects in spite of this initial limited variance—and included control variables, and time and condition main effects, in our model—our results suggest that the effects of community-engaged greening (and greening more generally) might be particularly strong. In addition, a small effect may have significant health consequences as researchers have found that detrimental health and mental health sequelae are associated with victimization and exposure to community violence ( Goldstick et al, 2018 ; Heinze et al, 2017 ; Hsieh et al, 2017 , 2021 ; Lee et al, 2020 ). Thus, reduced exposure to even a single violent event can have important health consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Since we found time by condition interaction effects in spite of this initial limited variance—and included control variables, and time and condition main effects, in our model—our results suggest that the effects of community-engaged greening (and greening more generally) might be particularly strong. In addition, a small effect may have significant health consequences as researchers have found that detrimental health and mental health sequelae are associated with victimization and exposure to community violence ( Goldstick et al, 2018 ; Heinze et al, 2017 ; Hsieh et al, 2017 , 2021 ; Lee et al, 2020 ). Thus, reduced exposure to even a single violent event can have important health consequences.…”
Section: Discussionmentioning
confidence: 99%
“…When these facets of violence were assessed in the first block of the regression model, only direct violence exposure was significantly linked to resilience, such that less direct violence was associated with higher resilience. Previous literature has examined rates and effects of cumulative violence exposure among YOC without accounting for variability based on types of violence (e.g., Antunes & Ahlin, 2021;Frazer et al, 2018;Hsieh et al, 2021;Slopen et al, 2016). Few studies have analyzed the potential for direct and indirect violence to have differential relations to resilience.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hsieh and colleagues (2021) found that exposure to direct and indirect violence among African American youth may increase psychological and physiological stress. Previous literature has typically combined direct and indirect violence, assessing it cumulatively (Antunes & Ahlin, 2021;Frazer et al, 2018;Hsieh et al, 2021;Slopen et al, 2016). However, some literature suggests that direct and indirect violence may differentially affect youths' functioning (Elsaesser, 2018;Zeringue, 2019;Zimmerman & Posick, 2016).…”
Section: Violence Exposure Among Yocmentioning
confidence: 99%
“…In addition to serious physical health consequences and risk of death (Wright et al, 2017), Black adolescents’ community violence exposure has been linked with depressive, anxious, and post‐traumatic stress symptoms, as well as externalizing behaviors ranging from impulsivity and aggression to conduct problems and substance use (Fowler et al, 2009). Troubling in their own right, each of these internalizing and externalizing concerns during adolescence has been shown to forecast difficulties in social, academic, and physical health domains enduring in adolescence and into adulthood (Hsieh et al, 2021; Loomis et al, 2020). In addition, community and population‐based research highlights community violence exposure as a risk for youth's suicide ideation and attempts (see Castellví et al, 2017 for a review), though research focused exclusively on Black youth is limited.…”
Section: Black Youth Suicidementioning
confidence: 99%